Paths linking maternal resources for care to child growth and early childhood development in Bangladesh (P11-125-19) - Basnet, Sulochana; Frongillo, Edward A.; Nguyen, Phuong Hong; Moore, Spencer; Arabi, Mandana (Oxford University Press, 2019)
The study aimed to determine the paths through which resources for care were associated with child growth and development. We hypothesized that resources could have been directly associated with child outcomes or indirectly through care behaviors. Child growth could also have mediated the association between care resources and development.